Site‐Selective In Situ Grown Calcium Carbonate Micromodels with Tunable Geometry, Porosity, and Wettability. (20th May 2016) - Lee, Seung Goo; Lee, Hyundo; Gupta, Ankur; Chang, Sehoon; Doyle, Patrick S.
Abstract : Micromodels with simplified porous microfluidic systems are widely used to mimic the underground oil‐reservoir environment for multiphase flow studies, enhanced oil recovery, and reservoir network mapping. However, previous micromodels cannot replicate the length scales and geochemistry of carbonate because of their material limitations. Here a simple method is introduced to create calcium carbonate (CaCO3 ) micromodels composed of in situ grown CaCO3 . CaCO3 nanoparticles/polymer composite microstructures are built in microfluidic channels by photopatterning, and CaCO3 nanoparticles are selectively grown in situ from these microstructures by supplying Ca 2+, CO3 2− ions rich, supersaturated solutions. This approach enables us to fabricate synthetic CaCO3 reservoir micromodels having dynamically tunable geometries with submicrometer pore‐length scales and controlled wettability. Using this new method, acid fracturing and an immiscible fluid displacement process are demonstrated used in real oil field applications to visualize pore‐scale fluid–carbonate interactions in real time. Abstract : Calcium carbonate (CaCO3 ) micromodels are fabricated by a photolithographic technique and by a subsequent in situ growth of CaCO3 . The fast and selective growth of CaCO3 on the multiple CaCO3 posts in a microchannel requires providing well‐controlled Ca 2+, CO3 2− ions rich/supersaturated solutions.